Microbiota plasticity in tilapia gut revealed by meta-analysis evaluating the effect of probiotics, prebiotics, and biofloc - Marcel Martinez-Porchas; Aranza Preciado-Álvarez; Francisco Vargas-Albores; Martina Hilda Gracia-Valenzuela; Francesco Cicala; Luis Rafael Martinez-Cordova; Diana Medina-Félix; Estefania Garibay-Valdez (PeerJ, 2023)
Tilapia species are among the most cultivated fish worldwide due to their biological advantages but face several challenges, including environmental impact and disease outbreaks. Feed additives, such as probiotics, prebiotics, and other microorganisms, have emerged as strategies to protect against pathogens and promote immune system activation and other host responses, with consequent reductions in antibiotic use. Because these additives also influence tilapia’s gut microbiota and positively affect the tilapia culture, we assume it is a flexible annex organ capable of being subject to significant modifications without affecting the biological performance of the host. Therefore, we evaluated the effect of probiotics and other additives ingested by tilapia on its gut microbiota through a meta-analysis of several bioprojects studying the tilapia gut microbiota exposed to feed additives (probiotic, prebiotic, biofloc). A total of 221 tilapia gut microbiota samples from 14 bioprojects were evaluated. Alpha and beta diversity metrics showed no differentiation patterns in relation to the control group, either comparing additives as a group or individually. Results also revealed a control group with a wide dispersion pattern even when these fish did not receive additives. After concatenating the information, the tilapia gut core microbiota was represented by four enriched phyla including Proteobacteria (31%), Fusobacteria (23%), Actinobacteria (19%), and Firmicutes (16%), and seven minor phyla Planctomycetes (1%), Chlamydiae (1%), Chloroflexi (1%), Cyanobacteria (1%), Spirochaetes (1%), Deinococcus Thermus (1%), and Verrucomicrobia (1%). Finally, results suggest that the tilapia gut microbiota is a dynamic microbial community that can plastically respond to feed additives exposure with the potential to influence its taxonomic profile allowing a considerable optimal range of variation, probably guaranteeing its physiological function under different circumstances.